Pancreatic β-cell regeneration in situ by the ALK3 agonist THR-123 - Silvia Álvarez-Cubela; Isabella D. Altilio; Mayur Doke; Dagmar Klein; Alejandro Tamayo; Óscar Alcázar; Carlos García Santana; Mirza Muhammad Fahd Qadir; Charles García Alver; Francis Cruz; Olivia Biggs; Jorge David Tovar Castro; et al. (Nature Communications)
Abstract The demonstration that BMP signaling activates progenitor-like populations within pancreatic ducts supports the potential use of BMP receptor agonists to induce islet neogenesis in situ. In this context, we tested the ability of THR-123, a cyclic peptide with BMP-7-like activity, to regenerate β-cell mass in diabetic mice. We show here that treatment with THR-123 reduces hyperglycemia through the rapid formation of new BrdU-labeled islets, many in apposition to ducts. These islets, unlike those from non-diabetic controls, feature an extensive intrainsular network of ductal tissue. The earlier stages of THR-123-induced β-cell formation were reproduced in live pancreatic slices, an organotypic model that allowed us to visualize ductal cells transitioning to glucose-responsive insulin-expressing cells in real time. scRNAseq analyses further suggest that this transition occurs through a hybrid ducto-acinar stage similar to that previously reported in humans. Taken together, our data support the conclusion that these islets arise predominantly by neogenesis. These results pave the way for the design of pharmacological strategies to treat insulin-dependent diabetes.